Analysis of Malathion Insecticide Resistance in Aedes aegypti Mosquitoes Using the CDC Bottle Bioassay Method - Kirche, Agnes Angelina; Kurniawan, Betta; Putri, Giska Tri; Mutiara, Hanna (Medula, 2025)
Dengue is an infectious disease transmitted by the Aedes aegypti mosquito, which breeds rapidly in Indonesia's tropical environment, increasing the risk of spreading this disease. Vector control using malathion insecticide can be effective, but repeated use and inappropriate dosage can cause resistance in mosquitoes which ultimately increases the risk of dengue infection. CDC Bottle Bioassay is a test method for evaluating mosquito resistance to insecticides with a standardized procedure and is carried out using bottles containing insecticides with different diagnostic doses. Research using this method shows that Aedes aegypti mosquitoes in various locations show resistance to malathion at certain doses and tolerance at other doses. Several studies have also shown that mosquitoes exposed to malathion show categories of resistance or tolerance based on the mortality rate recorded during the test. Malathion, which is a class of organophosphorus insecticides, works by irreversibly binding to acetylcholinesterase and effectively kills mosquitoes, but repeated use can trigger resistance. Factors influencing resistance include biological factors such as migration, operational factors such as insecticide dosage and application, as well as genetic factors associated with the resistant allele. If mosquitoes carrying resistant alleles move or interbreed, this can increase the resistance status in an area, which is seen in Aedes aegypti populations in several regions of the world.